Autonomous production of granulocyte-colony stimulating factor in tumour xenografts associated with leukocytosis. - Katoh, Y. (Nature Publishing Group, 1993)
Leukocytosis sometimes accompanies malignant neoplasms in the absence of infection. It is thought that the production of colony-stimulating factor by neoplasms is the most potent cause of tumour-induced leukocytosis; several mechanisms have been suggested to explain this. We examined 155 human tumour xenografts established in nude mice, and found that 17 of the xenografts induced remarkable leukocytosis (> 15,000 microliters-1) in nude rats. We examined granulocyte colony-stimulating factor (G-CSF) production by the xenografts to study the mechanisms underlying this tumour-induced leukocytosis. Ten of the 17 xenografted human tumours appeared to express the G-CSF gene. Serum G-CSF increased, to concentrations of 179-37,218 pg ml-1, in host animals transplanted with the ten xenografts expressing the G-CSF gene transcripts. The biological activity of serum G-CSF also increased, to concentrations of 206-9,074 pg ml-1, in the host animals transplanted with the ten xenografts. Immunohistochemical analysis demonstrated G-CSF production at the cellular level in three of the ten xenografts. These results suggested that the production of G-CSF is a common event in human tumour xenografts associated with leukocytosis, but that factors other than G-CSF are also likely to be involved. Leukocytosis induced by neoplasms seems to be a heterogeneous and complex disorder. IMAGES: